Third-day weight changes and bronchopulmonary dysplasia risk in preterm infants: a cohort study - Wenqian Chen; Wenhong Cai; Zhen Lin; Xiaofeng Ye; Bingjie Chen; Susu Mei; Tingting Huang; Yanli Ren (Frontiers in Pediatrics)
ObjectiveFluid balance and weight changes in the early postnatal period are critical indicators of neonatal adaptation and have been implicated in the development of complications in preterm infants. However, the relationship between early weight changes and the risk of bronchopulmonary dysplasia (BPD) remains unclear. This study aimed to evaluate the association between weight change by the third day of life and the subsequent risk of BPD in preterm infants.Study DesignA retrospective cohort study included preterm infants <32 weeks gestation or <1,500 g birth weight. Logistic regression was used to assess the association between weight change by day 3 (percentage change from birth weight) and BPD.ResultsAmong 453 infants, 97.4% (n = 441) had weight changes between −15% and 5%, with a BPD incidence of 34.2%. Each 1% increase in weight change by day 3 was linked to a 10% increase in BPD risk (OR = 1.10, 95% CI: 1.03–1.18). Infants without weight loss had a 2.52-fold higher BPD risk (OR = 2.52, 95% CI: 1.34–4.80).ConclusionWeight loss byday 3 is associated with a lower BPD risk in preterm infants. The day 3 weight change is a noninvasive and simple early predictor of BPD, and optimizing early fluid management to guide appropriate weight changes may help reduce BPD incidence.